Kinetics of phloretin binding to phosphatidylcholine vesicle membranes (The Rockefeller University Press, 1980)
The submillisecond kinetics for phloretin binding to unilamellar phosphatidylcholine (PC) vesicles was investigated using the temperature-jump technique. Spectrophotometric studies of the equilibrium binding performed at 328 nm demonstrated that phloretin binds to a single set of independent, equivalent sites on the vesicle with a dissociation constant of 8.0 microM and a lipid/site ratio of 4.0. The temperature of the phloretin-vesicle solution was jumped by 4 degrees C within 4 microseconds producing a monoexponential, concentration-dependent relaxation process with time constants in the 30--200-microseconds time range. An analysis of the concentration dependence of relaxation time constants at pH 7.30 and 24 degrees C yielded a binding rate constant of 2.7 X 10(8) M-1 s-1 and an unbinding constant of 2,900 s-1; approximately 66 percent of total binding sites are exposed at the outer vesicle surface. The value of the binding rate constant and three additional observations suggest that the binding kinetics are diffusion limited. The phloretin analogue, naringenin, which has a diffusion coefficient similar to phloretin yet a dissociation constant equal to 24 microM, bound to PC vesicle with the same rate constant as phloretin did. In addition, the phloretin-PC system was studied in buffers made one to six times more viscous than water by addition of sucrose or glycerol to the differ. The equilibrium affinity for phloretin binding to PC vesicles is independent of viscosity, yet the binding rate constant decreases with the expected dependence (kappa binding alpha 1/viscosity) for diffusion-limited processes. Thus, the binding rate constant is not altered by differences in binding affinity, yet depends upon the diffusion coefficient in buffer. Finally, studies of the pH dependence of the binding rate constant showed a dependence (kappa binding alpha [1 + 10pH-pK]) consistent with the diffusion-limited binding of a weak acid.